1994
DOI: 10.1109/20.333953
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion and grain isolation in Co/Cr thin films

Abstract: A bstact--In this work, interdiffusion and grain isolation in Co/Cr films have been investigated by studying the dependence of the magnetic properties on the substrate preheating temperature as well as on post-deposition annealing processes. By choosing pure CO instead of a Co-alloy, the possibility of grain isolation caused by the segregation of solute atoms from within the magnetic layer has been eliminated. It is found that both post-deposition thermal annealing and substrate preheating can effectively incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There are several approaches to obtain high coercivity and low noise. The most common one involves segregation of non-magnetic materials such as Cr to the grain boundaries of the Co-based alloy films [1][2][3][4][5][6][7][8] or post-deposition annealing that promotes Cr diffusing from the Cr underlayer into the CoCrPt layer [9,10]. These methods allow the CoCrPt film systems to achieve enhanced H c , and reduction of intergrain coupling and hence noise reduction [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches to obtain high coercivity and low noise. The most common one involves segregation of non-magnetic materials such as Cr to the grain boundaries of the Co-based alloy films [1][2][3][4][5][6][7][8] or post-deposition annealing that promotes Cr diffusing from the Cr underlayer into the CoCrPt layer [9,10]. These methods allow the CoCrPt film systems to achieve enhanced H c , and reduction of intergrain coupling and hence noise reduction [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Other elements such as Ta, Nb, B are believed to reduce the exchange coupling. It is not clear whether these or other elements actually segregate to the Co alloy grain boundaries or if they drive other alloying elements (such as Cr) to do so, which in turn provides for the magnetic isolation of the grains [18,19].…”
Section: Chemical Segregationmentioning
confidence: 99%
“…It has been reported that in Co/Cr layers, a post-deposition thermal treatment induces interdiffusion of metal atoms and allows the Co grain to segregate within the solid solution, this phenomenon being responsible for the increase of sample coercivity [6]. Annealed samples bear more resemblance to solid solutions than layered systems; however, the annealing process may result in undesired alteration of sample morphology and must be studied in detail.…”
Section: Introduction and Experimentalmentioning
confidence: 99%